2018
DOI: 10.1002/admi.201701491
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Growth of Large 2D Silver Nanosheets by Highly Ordered Biological Template at Air/Gel Interface

Abstract: However, dislocations, disinclinations, and symmetry-breaking instabilities can frequently prompt the formations of defects and grain boundaries in the synthesis processes [15,16] and crystal growth rate of the 2D nanostructure is very slow. [17,18] In nature system, organic-inorganic hybrid nanostructures with high-crystallinity and diverse morphologies can be constructed by biomineralization process. [19,20] This natural process can efficiently induce the molecular rearrangement for high complexity [21] and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…On the other hand, the infused precursor solution with gelatin formed a continuous morphology on the porous SSC cathode backbone, instead of agglomerated particles. The non-agglomerated surface can be related to the crystal growth of metal oxide between the confined complex layers, which was reported in previous research 9 . Since the metallic ions were captured by the side chains of gelatin molecule, such as amide, hydroxyl, and carboxyl groups, the metallic ions can be partially condensed to form membranes by salting out effect during the evaporation process 21 .…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…On the other hand, the infused precursor solution with gelatin formed a continuous morphology on the porous SSC cathode backbone, instead of agglomerated particles. The non-agglomerated surface can be related to the crystal growth of metal oxide between the confined complex layers, which was reported in previous research 9 . Since the metallic ions were captured by the side chains of gelatin molecule, such as amide, hydroxyl, and carboxyl groups, the metallic ions can be partially condensed to form membranes by salting out effect during the evaporation process 21 .…”
Section: Resultssupporting
confidence: 63%
“…Due to its superior properties, gelatin has been employed as a base material for bio-applications and binding material for the synthesis of inorganic compounds. Seong et al reported a dense 2-dimensional metal structure by applying self-layering and crystallization of metal-ion/gelatin complex 9 . In addition, Wang et al demonstrated a homogeneous polymer/metal complex system by applying calcined gelatin-based iron precursor solution to control the metal oxide/carbon hybrid structure 10 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Due to their biocompatibility and functional side-chains, the hydrogelbased assembly process can be applied to various academic and industrial fields, such as crystal fabrication [5,6] and biomedical applications. [11] According to the mechanism, it was demonstrated that the biological template can be used for aligning the molecular orientation in the synthesis of the highquality nanostructure. Jang et al have reported the fabrication of layer-by-layer structured single crystalline nanomaterials within several minutes by gelatin.…”
Section: Introductionmentioning
confidence: 99%
“…Dimensional reduction of 3D materials to 0D, 1D, or 2D nanostructures (thickness vs lateral size < 1%), has attracted interest for discovering intriguing new catalytic properties. Notably, including 2D nanostructures comprised of metals, transition metal dichalcogenides, transition metal oxides, and 2D transition metal carbides (TMCs) have been explored for enhanced catalytic performance, and advances in this area have led to reliable and cost‐effective fabrication methods ideal for base‐metal hydrogen evolution catalysts.…”
Section: Summary Of Catalyst Activity Of Different Carbides For Her Imentioning
confidence: 99%
“…The process parameters (concentration, peptide selection, and temperature) can be carefully controlled to enable the preparation of hydrogel materials containing 0D particles, 1D tubes, or 2D lamellar products . These self‐assembling soft structures are amenable to subsequent transformation by thermal and chemical approaches . By selecting carbide‐forming metals, a nanostructured hydrogel can be prepared that is amenable for subsequent conversion into TMCs that retain their supramolecular dimensionality.…”
Section: Summary Of Catalyst Activity Of Different Carbides For Her Imentioning
confidence: 99%